Trends in and principles of training vocational teachers - I. Zyrianova, Natalia; M. Dorozhkin, Evgeny; V. Zaitseva, Yekaterina; S. Korotayer, Ivan; D. Shcherbin, Matvey (International Journal of Engineering and Technology, 2018)
The urgency of the problem under consideration here has been necessitated by a need for training more vocational teachers for the system; they are to be specialists in developing and implementing the basic and optional educational programs designed for workshop force and mid-tier specialists; this means preparing the personnel resource for innovation industry. The goal of the paper is to reveal the changes that are necessary to be brought about for improving the quality of training delivered to students of vocational pedagogy and continuing vocational education. The key approach to the study of the problem is the systems activity approach that allows us to employ the systems concepts for building domain-specific schema linked to the investigation of how vocational teacher training is organized today, with regard to the requirements set by Russia's educational standard "Teacher of vocational training and continuing vocational education". Analysis of theory and findings in the literature led us to the conclusion that, considering the particular properties and logic of vocational teacherâ€™s education, as well as reliance on the approaches and concepts under consideration, is what shall cater to the ever increasing demands to it from man, society and state. In view of the analysis' results, we suggest recommendations for improving vocational teacher training that would lead to vocational education/training/continuing education quality enhancement, including training offered in corporate training centers and innovation industries. The materials herein may be of value to educational managers in forming their personnel resource.Â Â